2017
DOI: 10.1002/ird.2124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applying Sewage Effluent with Subsurface Drip Irrigation on Soil Enzyme Activities during the Maize Growing Season

Abstract: Subsurface drip irrigation is an appropriate method when using sewage effluent for crop irrigation, but its resultant heterogeneous distribution of water and nutrients in the soil may affect enzyme activities (EAs). Field experiments were designed, with three lateral depths at 0, 15, and 30 cm beneath the soil surface and three irrigation levels of 70, 100, and 130% of evapotranspiration, to investigate the effects of lateral depth, irrigation level, and water quality on the EAs of alkaline phosphatase, urease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A few studies have found that soil pH decreased with salinity accumulation, and there was a significant negative correlation between them (Yin et al 2011;Qiu et al 2017a;Li 2020). Nevertheless, the effects of irrigation level on the distribution of E. coli and soil enzyme activities in soil were unnoticeable and unstable during the experimental periods when applying TSE with drip irrigation Qiu et al 2017a). It may reasonably be expected that more efforts should be made to find the mechanism behind these phenomena.…”
Section: Irrigation Amountmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have found that soil pH decreased with salinity accumulation, and there was a significant negative correlation between them (Yin et al 2011;Qiu et al 2017a;Li 2020). Nevertheless, the effects of irrigation level on the distribution of E. coli and soil enzyme activities in soil were unnoticeable and unstable during the experimental periods when applying TSE with drip irrigation Qiu et al 2017a). It may reasonably be expected that more efforts should be made to find the mechanism behind these phenomena.…”
Section: Irrigation Amountmentioning
confidence: 99%
“…The activities of alkaline phosphatase, urease, and invertase all decreased with increasing horizontal and vertical distance from the emitter in a saline sodic soil while using drip irrigation (Kang et al 2013). The effects of lateral depth, irrigation level, and water quality on soil enzyme activities were evaluated by Qiu et al (2017a). Their results indicated that a greater lateral depth resulted in noticeably higher enzyme activities in deeper soils, while enzyme activities at a shallow lateral depth were higher in topsoil.…”
Section: Impacts Of Tse Drip Irrigation On Soil Biological Activitiesmentioning
confidence: 99%
“…Subsurface irrigation defined by Camp (1998) is the method of applying irrigation water directly into the root zone of the soil profile. In contrast with surface irrigation systems, subsurface irrigation systems highly reduce human contact with irrigation water which sometimes is not freshwater (Qiu et al, 2017). According to Massatbayev et al (2016) the main components structured the properties of subsurface irrigation are emission products, construction methods, materials, and packing of the soil.…”
Section: Introductionmentioning
confidence: 99%